Extended Hildebrand solubility approach applied to some sulphonamides in propylene glycol + water mixtures (2015)
Extended Hildebrand solubility approach (EHSA) was applied to evaluate the solubility of sulphanilamide, sulphapyridine and sulphamethizole in some propylene glycol + water mixtures at 298.15 K. Reported experimental solubility and some properties...